Distributionally robust frequency dynamic constrained unit commitment considering uncertain demand-side resources. (1st February 2023) - Yang, Yang; Peng, Jimmy Chih-Hsien; Ye, Zhi-Sheng
Abstract: Demand-side resources (DSR) have been considered as flexible frequency reserve providers in power systems. Given their uncertain nature in the reserve deployment and the load recovery periods, it is necessary to consider these uncertainties in the frequency dynamic constrained unit commitment (FDUC) model. This paper proposes a two-stage distributionally robust FDUC model to minimize the worst-case cost expectation under a set of probability distributions of DSR uncertainties, which are restricted by the supports and moments generated from statistical information. In addition, the cumulative frequency deviation during the entire regulation period is exploited as a frequency dynamic criterion. Particularly, it can quantify the regulation efficacy of the reserve resources with diverse frequency response characteristics, such as the dead-band time and the reserve delivery time. Simulations based on the IEEE 118-bus and 300-bus systems validate the effectiveness of the proposed method in hedging against the DSR uncertainties. Highlights: A frequency dynamic unit commitment model considering uncertain demand-side resources (DSR). The uncertainty of demand-side resources is captured by a moment-based ambiguity set. A criterion reflecting the efficacy of different frequency regulation resources. The load recovery property of demand-side resources diminishes their fast response advantage. below is the edited version: A frequency dynamic unit commitment model with uncertain demand-side resources. The uncertainty of demand-side resources is captured by a moment-based ambiguity set. A criterion reflecting the efficacy of different frequency regulation resources. Load recovery diminishes the fast response advantage of demand-side resources.